2002
DOI: 10.1108/09596110210424501
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of present and future competencies required for club managers

Abstract: Compares the findings of two studies conducted to investigate the ranking of content domain areas of club management and management competencies necessary for success in private club management. A comparison is made between rankings for present and future success. The findings indicate areas for individual manager preparation and organizational program development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 8 publications
(9 reference statements)
1
39
0
Order By: Relevance
“…As noted earlier, while previous research has addressed the competencies required for leadership effectiveness in clubs, hotels, casinos, restaurants, and other segments (Brownell, 2004;Choi, 2006;Enz, 2003;Perdue et al, 2002), virtually no studies have focused specifically on the cruise industry as an organizational context. The unique aspects of the shipboard environment-Stewart's demands and constraints-suggest that skills and attributes/abilities may be distinctive.…”
Section: Micro Dimensions Of Cruise Contextmentioning
confidence: 94%
See 1 more Smart Citation
“…As noted earlier, while previous research has addressed the competencies required for leadership effectiveness in clubs, hotels, casinos, restaurants, and other segments (Brownell, 2004;Choi, 2006;Enz, 2003;Perdue et al, 2002), virtually no studies have focused specifically on the cruise industry as an organizational context. The unique aspects of the shipboard environment-Stewart's demands and constraints-suggest that skills and attributes/abilities may be distinctive.…”
Section: Micro Dimensions Of Cruise Contextmentioning
confidence: 94%
“…For instance, Tracey and Hinkin (1994), conclude that effective communication is particularly critical in service environments as managers gain commitment and align employee's perspectives so that standards of service excellence can be defined and met. Other studies have examined competency requirements in such industry segments as catering firms and airlines (Brownell and Reynolds, 2000;Wilson et al, 2000), hotels and restaurants (Kay and Moncarz, 2004;Okeiyi et al, 1994), and clubs (Perdue et al, 2002).…”
Section: Article In Pressmentioning
confidence: 99%
“…Barrows and Walsh (2002), for example, observed that the lack of knowledge of the private club industry, in general, was also reflective of the lack of research publications addressing current issues in the private club industry. Perdue et al (2000Perdue et al ( , 2001Perdue et al ( , 2002 were the first group of researchers who identified important competencies applied to private club managers. While they helped identify important competencies required for successful private club managers, these previous studies failed to address some of the most important managerial knowledge, skills, and abilities necessary for effective club management.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is suggested to consider facility operation process during the planning and maintenance stage, which increase the attractiveness of facility environment as a result. Perdue et al (2002) identify one of the competence areas is building and facility management, which are in a higher rank from a survey of the club management association members in the USA in 2002.…”
Section: Physcial Environmental Considerations For Sports and Leisurementioning
confidence: 99%